Price behaviour of coconut in major markets of Kerala: A time series analysis - Preethi VP; Jesy Thomas K; Anil Kuruvila; Laly John C and Phuge SC
Changes in the price behaviour of coconut in major markets of Kerala (Alappuzha and Kozhikode) were analysed for two periods viz., Period I (from 1980-01 to 1995-96) and Period II (from 1996-97 to 2015-16) and the variations in price due to trend, cyclical, seasonal and irregular fluctuations were calculated. There was considerable and distinctly different seasonality in the price of coconut in Alappuzha and Kozhikode markets for both the periods. In spite of high fluctuations, coconut price in the long run had shown an increasing trend in both Alappuzha and Kozhikode markets for both the periods. It was observed that the seasonality and irregular variations in the price were more prominent in the primary commodity than the processed commodity like copra